Pengembangan Produk Minuman Jelly Nira Kelapa dengan Quality Function Deployment [Coconut Sap Jelly Drink Product Development with Quality Function Deployment] - Ervina Mela; Gunawan Wijonarko (Buletin Palma, 2020)
Coconut sap is one of the agricultural commodity that can be processed into various products other than sugar. One of the products that potential to be developed is coconut sap jelly drink. To create successful coconut sap jelly drink on the market, it is necessary to develop products according to the needs of consumers. Quality function deployment (QFD) is a product development method that accommodates the needs of consumers, then connects them with appropriate production techniques. The purpose of this study was to determine the priority attributes of consumer requirements and technical parameters as the basis for designing a coconut sap jelly drink. The research method uses QFD, with questionnaires and expert interviews. Analysis of quality houses shows that the attributes of consumer requirements that are the priority in designing coconut juice jelly drinks are jelly viscosity such as Okki Jelly Drink (weight 8.72), easy to carry packaging (weight 8.49), purple color like grapes (weight 8.35 ), there is a taste content on the packaging label (8.30) and there is RDA information on the packaging label (weight 8.23), while the priority technical parameter is the preparation of other ingredients except coconut sap juice (weight 22.82%). Producers who will develop coconut sap jelly drink should pay attention to the viscosity of the jelly and preparation of raw materials including pectin, and sugar.ABSTRAKNira kelapa merupakan salah satu hasil pertanian yang dapat diolah menjadi berbagai produk selain gula. Salah satu produk yang potensial dikembangkan adalah minuman jelly nira kelapa. Supaya dapat dihasilkan produk minuman jelly nira kelapa yang sukses di pasaran maka perlu dilakukan upaya pengembangan produk sesuai keinginan/kebutuhan konsumen. Quality function deployment (QFD) merupakan metode pengembangan produk yang mengakomodasi kebutuhan dan keinginan konsumen, kemudian menghubungkannya dengan teknik  produksi yang tepat. Tujuan dari penelitian ini adalah untuk mengetahui prioritas atribut persyaratan konsumen dan parameter teknis sebagai dasar pengembangan produk minuman jelly nira kelapa. Metode penelitian menggunakan QFD, dengan penyebaran kuesioner  dan wawancara pakar.  Analisis rumah mutu menunjukkan persyaratan konsumen yang menjadi prioritas pada pengembangan minuman jelly nira kelapa adalah kekentalan jelly seperti Okki Jelly Drink (bobot 8,72), kemasan mudah dibawa (bobot 8,49), warna ungu seperti buah anggur (bobot 8,35), terdapat keterangan rasa pada label kemasan (8,30)  dan  terdapat informasi AKG pada label kemasan (bobot 8,23) sedangkan parameter teknis yang menjadi prioritas adalah persiapan bahan lain selain nira kelapa (bobot 22,82%).  Produsen yang akan mengembangkan minuman jelly nira kelapa sebaiknya memberikan perhatian utama pada kekentalan jelly dan persiapan bahan baku selain nira di antaranya pektin, dan gula.